2019
DOI: 10.1136/ijgc-2019-000263
|View full text |Cite
|
Sign up to set email alerts
|

Staging early cervical cancer in China: data from a multicenter collaborative

Abstract: BackgroundIn 2018 the International Federation of Gynecology and Obstetrics (FIGO) revised the staging system of cervical cancer. This study aimed to assess the quality of staging early cervical cancer in China before the revision.MethodsThis multicenter retrospective study included 34 tertiary hospitals in China. Medical records of patients with cervical cancer who underwent primary surgical treatment between January 2010 and December 2015 were reviewed retrospectively. All patients were clinically staged acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The authors concluded that the quality of staging cervical cancer was suboptimal before the integration of advanced imaging techniques as currently proposed by the 2018 FIGO staging system. 18 The evidence thus suggests that clinical examination, although a standard and necessary step in the initial evaluation of patients with cervical cancer, is limited in its ability to reliably ascertain tumor size with accuracy. It is imperative that in addition to the pelvic examination, tools such as imaging studies are used to complement the information gathered in designating stage and implementing management strategy (Table 1).…”
Section: Physical Examinationmentioning
confidence: 99%
“…The authors concluded that the quality of staging cervical cancer was suboptimal before the integration of advanced imaging techniques as currently proposed by the 2018 FIGO staging system. 18 The evidence thus suggests that clinical examination, although a standard and necessary step in the initial evaluation of patients with cervical cancer, is limited in its ability to reliably ascertain tumor size with accuracy. It is imperative that in addition to the pelvic examination, tools such as imaging studies are used to complement the information gathered in designating stage and implementing management strategy (Table 1).…”
Section: Physical Examinationmentioning
confidence: 99%
“…Clinical data were collected from patient files and the medical record management system in the hospitals by trained gynecological oncology staff using standardized data collection and quality control procedures. The details of the data sources and methods were the same as previously reported ( 22 , 23 ). For patients undergoing surgical treatment, the collected data, including the demographic details, preoperative examination results, surgical information, pathological results, preoperative, and postoperative adjuvant treatment details, complications, hospitalization time, and expenses, and follow-up, contained almost all the information during the treatment of cervical cancer.…”
Section: Methodsmentioning
confidence: 99%
“…The C4 survey database comprises data on a total of 46 313 women with cervical cancer who were treated between January 1, 2004, and December 31, 2016, in 37 medical institutions in mainland China. Details of the data collection strategy have been described in previous studies 13‐16 . In brief, data collection was carried out by gynecologists using the medical record management system of each hospital.…”
Section: Methodsmentioning
confidence: 99%